Intracellular translocation of fluorescent sphingolipids in cultured fibroblasts: endogenously synthesized sphingomyelin and glucocerebroside analogues pass through the Golgi apparatus en route to the plasma membrane (The Rockefeller University Press, 1985)
When monolayer cultures of Chinese hamster lung fibroblasts are briefly incubated at 2 degrees C with the fluorescent sphingolipid analogue, C6- NBD-ceramide (N- [7-(4-nitrobenzo-2-oxa-1,3-diazole)] aminocaproyl sphingosine), fluorescent labeling of the mitochondria, endoplasmic reticulum, and nuclear envelope occur. During further incubation at 37 degrees C, the Golgi apparatus, and later the plasma membrane, become intensely fluorescent. Within this period, the C6-NBD-ceramide is converted to equal amounts of fluorescent sphingomyelin and glucocerebroside (Lipsky, N. G., and R. E. Pagano, 1983, Proc. Natl. Acad. Sci. USA., 80:2608-2612). In the present study, the intracellular translocation of these metabolites and their subsequent appearance at the plasma membrane were investigated by fluorescence microscopy, the addition of the ionophore monensin, and the technique of "back exchange," in which the amounts and types of fluorescent lipids present at the cell surface are identified after their transfer from the cell surface into recipient vesicles. In control cells, the amount of fluorescent glucocerebroside and sphingomyelin that could be removed from the cell surface by back exchange increased during incubation at 37 degrees C, correlating with the increased fluorescence of the plasma membrane observed by microscopy. In the presence of 10 microM monensin, visible labeling of the plasma membrane was greatly diminished, whereas the Golgi apparatus became highly fluorescent and distended. The ability to remove fluorescent metabolites from the cell surface by back exchange was significantly but reversibly inhibited by monensin. Monensin also increased the total amount of fluorescent sphingomyelin, but not the glucocerebroside found in cells. Subcellular fractions were assayed for their ability to convert radiolabeled and fluorescent ceramides to the corresponding sphingomyelins and glucocerebrosides. The activities of parallel fractions coincided, suggesting that the presence of the NBD moiety did not affect the cellular metabolism of ceramide. Furthermore, the major peak of sphingomyelin- and glucocerebroside-synthesizing activity appeared to coincide with an enriched Golgi fraction. These results strongly suggest that fluorescent sphingomyelin was not synthesized at the plasma membrane as has recently been suggested for endogenous sphingomyelin. Rather, both the sphingomyelin and glucocerebroside analogues were synthesized intracellularly from C6-NBD-ceramide and translocated through the Golgi apparatus to the cell surface.